2005
DOI: 10.1183/09031936.05.00089304
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages induce an allergen-specific and long-term suppression in a mouse asthma model

Abstract: Increasing evidence suggests that macrophages (Mw) play a crucial downregulatory role in the initiation and progression of allergic asthma. Recently, the current authors demonstrated that ovalbumin (OVA)-loaded Mw (OVA-Mw) suppress subsequent OVA-induced airway manifestations of asthma and that this effect could be potentiated upon selective activation. In the present study, the authors further delineated the underlying pathway by which Mw exert this immunosuppressive effect.To examine the migration of OVA-Mw,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 38 publications
0
7
1
2
Order By: Relevance
“…S5). Extensive effects of IL‐10 on macrophages have been previously described and allergic airway inflammation in mice has been previously reported to be suppressed/regulated by macrophages . In addition, lung‐resident tissue macrophages have been suggested to promote airway tolerance by generating Treg .…”
Section: Discussionmentioning
confidence: 99%
“…S5). Extensive effects of IL‐10 on macrophages have been previously described and allergic airway inflammation in mice has been previously reported to be suppressed/regulated by macrophages . In addition, lung‐resident tissue macrophages have been suggested to promote airway tolerance by generating Treg .…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, macrophages are recruited to the airways of allergic subjects following allergen challenge [61]. They secrete cytokines and chemokines, including IL-1, IFN-␥, TNF-␣, IL-6, CCL2, CCL3, and CXCL8 [62,63], what results in the recruitment and activation of other inflammatory cells [64]. IL-6 is involved in macrophage differentiation [65].…”
Section: Macrophagesmentioning
confidence: 99%
“…It was apparent that AMs from unsensitized mice, which are not antigen-primed and have better regenerative capacity, provided protection against asthmatic symptoms [43,44]. Vissers et al [45] further demonstrated that intravenously administered allergen-loaded macrophages accumulate in the spleen and induce indirect, but long-term, allergen-specific immunosuppressive effects through regulatory T cells (Tregs). Similar observations have been made in human asthmatic studies where suppression of T cell proliferation by AMs is thought to be mediated through cell-cell interactions [46].…”
Section: Fungal Asthma-associated Inflammationmentioning
confidence: 97%